France : 2011 Article IV Consultation: Staff Report; Staff Statement; and Public Information Notice on the Executive Board Discussion. (IMF Staff Country Reports; Country Report ;, 2011)
Domestic demand is expected to remain the engine of growth in France, with net exports playing a minor role in the near term. Risks to the outlook are tilted to the downside. Boosting potential growth requires a comprehensive strategy. The consolidation targets set out in France's Stability Program and the multiyear budget framework strike the right balance between speed and sustainability. Financial stability risks seem contained but vigilance is required. The medium-term prospects for the economy depend on improved competitiveness.